Emaranhamento, dinâmica de não-equiíbrio e supercondutividade em sistemas de etétrons fortemente interagentes - Helena de Souza Braganca (2018)
The main goal of this thesis is the study of properties that emerge from the interaction between particles. (i) We describe many-body systems through quantities related to quantum information, (ii) study the nonequilibrium dynamics of closed quantum syste